Creative Arts Interventions to Address Depression in Older Adults: A Systematic Review of Outcomes, Processes, and Mechanisms - Dunphy, Kim; Baker, Felicity A.; Dumaresq, Ella; Carroll-Haskins, Katrina; Eickholt, Jasmin; Ercole, Maya; Kaimal, Girija; Meyer, Kirsten; Sajnani, Nisha; Shamir, Opher Y.; Wosch, Thomas (Frontiers in Psychology, 2019)
Depression experienced by older adults is proving an increasing global health burden, with rates generally 7% and as high as 27% in the USA. This is likely to significantly increase in coming years as the number and proportion of older adults in the population rises all around the world. Therefore, it is imperative that the effectiveness of approaches to the prevention and treatment of depression are understood. Creative arts interventions, including art, dance movement, drama and music modalities, are utilised internationally to target depression and depressive symptoms in older adults. This includes interventions led by trained arts therapists as well as other health and arts professionals. However, to date there has not been a systematic review that reports effects and examines the processes (why) and mechanisms (how) of creative arts interventions are used to address depression in this older age group. This systematic review of studies on creative arts interventions for older adults experiencing depression examined: outcomes of four creative arts modalities (art, dance movement, drama, and music); with particular attention paid to processes documented as contributing to change in each modality; and mechanisms considered to result from these processes. Our analysis of 75 articles (17 art, 13 dance, 4 drama and 41 music) indicates mostly significant quantitative or positive qualitative findings, particularly for interventions led by creative arts therapists. Mechanisms of change gleaned from the studies that were common across modalities include physical (e.g. increased muscle strength; neurochemical effects, such as endorphin release), intra-personal (e.g. enhanced self-concept, strengthened agency and mastery; processing and communication of emotions), cultural (e.g. creative expression, aesthetic pleasure), cognitive (e.g. stimulation of memory) and social (e.g. increased social skills and connection), that were all considered to contribute to reduced depression and symptoms. Recommendations for future research include a stronger focus on testing of processes and mechanisms.